Rancangan UI/UX Design Aplikasi Pembelajaran Bahasa Jepang Pada Sekolah Menengah Atas Menggunakan Metode Design Thinking - Muhammad Adhitya Dhita Pratama; Yudhi Raymond Ramadhan; Teguh Iman Hermanto (STMIK Budi Darma, 2022)
In the world of education that has developed, of course, we are indirectly required to be able to understand or master the use of foreign languages. SMA Negeri 1 Cikarang Pusat is one of the schools that learn Japanese. The students who study Japanese at the school have various kinds of great motivation, but also not a few of the students who can understand and even have difficulty in learning Japanese. Given that there are many innovations in the world of education in this era that involve technology to carry out the learning process. There are many ways to learn Japanese, for example by learning through learning media that utilize technology such as smartphones. Supported by increasingly advanced technological innovations and new interaction patterns, the role of the User Interface (UI) and User Experience (UX) is important to the needs of users in solving problems. This research was conducted to find out how we can meet and know user needs by using design thinking. With this Japanese language learning media, it is hoped that it can help students learn Japanese easily.